ISOLATION OF A COMPOUND FROM THE BULBS OF ELEUTHERINE BULBOSA (MILLER) URBAN (IRIDACEAE) - Vs, Rani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study is concerned with the detection, isolation, identification, and structural elucidation of the bioactive phytochemical from the bulbs of Eleutherine bulbosa. Methods: Ethyl acetate is the solvent used in Soxhlet extraction. Column chromatography and thin layer chromatography is employed in the isolation procedure. Identification and structural elucidation of the bioactive compound is determined using ultraviolet-visible (UV-vis), Fourier transform-infrared (FTIR) spectroscopy, liquid chromatographyâ€“mass spectrometry (LCMS-MS), and 1H nuclear magnetic resonance (1HNMR) spectroscopy. Results: A compound was isolated from the bulbs of E. bulbosa by solvent extraction and chromatography. UV-vis, FTIR spectroscopy, LCMS-MS, and 1HNMR studies showed that the isolated compound was bis (2-6,7-diamino-5,8-dioxo naphthalene-1yl) propanal. Conclusion: An yellowish-brown crystalline needle-shaped compound was isolated from the bulbs of E. bulbosa and characterized chemically. Spectroscopic analysis identified the compound as bis (2-6,7-diamino-5,8-dioxo naphthalene-1yl) propanal. Mass of the compound is m/z 244 (MH+=245).